2016
DOI: 10.1007/s10103-016-1891-1
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of Klebsiella pneumoniae biofilms and planktonic cells by 5-aminolevulinic acid and 5-aminolevulinic acid methyl ester

Abstract: Abstract:The treatment of Klebsiella pneumoniae, particularly extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae, is currently a great challenge. Photodynamic antimicrobial chemotherapy is a promising approach for killing antibiotic-resistant bacteria. The aim of this study was to evaluate the capacity of 5-aminolevulinic acid (5-ALA) and its derivative 5-ALA methyl ester (MAL) in the presence of white light to cause photodynamic inactivation (PDI) of K. pneumoniae planktonic and biofilm cells.In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…aPDI effectively eradicates a wide group of multidrug-resistant bacteria in vitro (planktonic and biofilm cultures), e.g., vancomycin-resistant Enterococcus faecalis (VRE) (5.37 log 10 unit reduction in survival) 12 , a methicillin-resistant S. aureus (MRSA) strain (5-6 log 10 unit reduction) 13 , and extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae. Effective biofilm reduction under aPDI was also documented 14 . A number of confirmatory studies on in vivo/ex vivo models have indicated the efficient reduction in viable bacterial cell numbers.…”
mentioning
confidence: 91%
“…aPDI effectively eradicates a wide group of multidrug-resistant bacteria in vitro (planktonic and biofilm cultures), e.g., vancomycin-resistant Enterococcus faecalis (VRE) (5.37 log 10 unit reduction in survival) 12 , a methicillin-resistant S. aureus (MRSA) strain (5-6 log 10 unit reduction) 13 , and extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae. Effective biofilm reduction under aPDI was also documented 14 . A number of confirmatory studies on in vivo/ex vivo models have indicated the efficient reduction in viable bacterial cell numbers.…”
mentioning
confidence: 91%
“…Only two experimental work concerns biofilm analysis upon aPDI treatment: with the use of 5-ALA/MAL and phenothiazines. Whereas in the first case appreciable efficacy of approximately 4 log 10 reduction (10 mM MAL) was obtained for both ESBL-producing and ESBL-nonproducing clinical isolate [34], there was only slight antibiofilm activity for each of phenothazines studied (TBO; Azure A, AA; and new methylene blue, NMB) [32].…”
Section: Klebsiella Sppmentioning
confidence: 92%
“…From the representatives of FDA-approved drugs, 5-ALA or MAL constitute an attractive option of PSs as their application resulted in more than 3 log 10 after application of 10 mM ALA. Of interest, ESBL-producing and ESBL-nonproducing strains were killed with similar efficacy. In case of MAL applications, the results were even better, and exceeded the value of 4 log 10 reduction in cell number [34]. The 5-ALA or MAL-based aPDI application seems to be attractive from the clinical point of view as beside the fact of the FDA/EMEA approval, these PSs can be used along with white light, which constitutes universal light source.…”
Section: Klebsiella Sppmentioning
confidence: 95%
“…Wells were stained with 0.1% crystal violet (CV) and resolubilized with 33% glacial acetic acid (19). K. pneumoniae (ATCC 700603) served as the biofilm positive control and media alone was the negative control (12,(23)(24)(25).…”
Section: Methodsmentioning
confidence: 99%